ECONOMIC REASONS FOR GENERIC CHOICE - N. P. Kutishenko; S. Y. Martsevich; S. N. Tolpygina; J. V. Lukina (Рациональная фармакотерапия в кардиологии)
Many generic medicines appear in the pharmaceutical market now. However, they are not always completely comparable with original drugs on efficacy and safety. In this article pharmacoeconomical estimation of some generics and original drugs was performed on example of therapeutic equivalency studies.